2011
DOI: 10.1007/s00384-011-1355-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of anorectal biofeedback for constipation

Abstract: While our sample was statistically underpowered, AB produced clinical improvements in constipation severity and QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 30 publications
1
41
2
Order By: Relevance
“…The pathogenic mechanisms are different for the different subtypes of DD, and the response to BFT may vary greatly between subtypes. Recent controlled studies have shown that BFT is an effective treatment for pelvic floor dyssynergia [15,42,43]; BFT was found to be superior to laxatives, with improvement being maintained over a long-term follow-up. The superior efficacy of BFT was also demonstrated by Wang et al [44] in their study of 50 CC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic mechanisms are different for the different subtypes of DD, and the response to BFT may vary greatly between subtypes. Recent controlled studies have shown that BFT is an effective treatment for pelvic floor dyssynergia [15,42,43]; BFT was found to be superior to laxatives, with improvement being maintained over a long-term follow-up. The superior efficacy of BFT was also demonstrated by Wang et al [44] in their study of 50 CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first application of BFT for treatment of CC due to DD was in 1987 [12]. Since then, a number of controlled studies have shown that BFT can be more effective than laxatives, muscle relaxants, and placebo, with benefits lasting for at least 12 months [13][14][15]. Based on these findings, BFT has been recognized as the most effective treatment for DD for several years [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The second mechanism, called PFD, is responsible for approximately 30-50% of cases of functional constipation (5). We should remember constipation in irritable bowel syndrome (7). In some cases, it is possible to perform biofeedback therapy involving manometric exercises of the external anal sphincter muscles.…”
Section: Discussionmentioning
confidence: 99%
“…However, an organic background of constipation is rare, and over 90% of constipation cases are the result of functional disorders, which can be diagnosed in accordance with the Rome III criteria (2,4,5). Treatment includes a high fiber diet, the proper education of patients, pharmacotherapy, and in some cases, biofeedback therapy (2,4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Prucalopride and other recently available prokinetic drugs are effective for some patients in short term [2], but their efficacy may not be sustained in the long term. Behavioural treatment (biofeedback) is effective for many patients in a randomized trial, but some remain symptomatic [3, 4]. …”
Section: Introductionmentioning
confidence: 99%